TV outside the box : trailblazing in the digital television revolution - Landau, Neil (Focal Press, 2016)
TV Outside the Box: Trailblazing in the Digital Television Revolution explores the new and exploding universe of on-demand, OTT (Over the Top) networks: Netflix, Amazon, Hulu, Crackle, CW Seed, Vimeo, AwesomenessTV, and many more. Featuring in-depth conversations with game-changing content creators, industry mavericks, and leading cultural influencers, TV Outside the Box is essential reading for anyone interested in the dynamics of a global media revolution - while it's happening. Readers will discover: How the new'disruptors'of traditional television models are shaping the future of the television and feature film business. You'll hear directly from the visionaries behind it all - from concept genesis to predictions for the future of streaming platforms; their strategies for acquisitions and development of new original content; and how the revolution is providing unprecedented opportunities for both established and emerging talent. What's different about storytelling for the progressive, risk-taking networks who are delivering provocative, groundbreaking, binge-worthy content, without the restraints of the traditional, advertiser-supported programming model. Through interviews with the showrunners, content creators, and producers of dozens of trailblazing series - including Orange Is the New Black, House of Cards, Transparent, and many more - you'll learn how and why the best and the brightest TV content creators and filmmakers are defining the new digital entertainment age - and how you can, too.